2006
DOI: 10.1891/0886-6708.21.4.483
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Partner Aggression Research: Impact of Laboratory Couples Conflict Protocols on Participants

Abstract: The impact of male-to-female intimate partner violence (IPV) research on participants is unknown. A measure of impact was given to participants in an IPV study to assess systematically the impact of completing questionnaires, engaging in conflict conversations, and being interviewed individually about anger escalation and de-escalation during the conversations. Participants completed the six question, Likert-scaled, impact measure. Both male and female participants rated the impact of the study as helpful to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Participants have experienced a decrease in intrusive thoughts over time when compared to a control group (Lutgendorf & Antoni, 1999) or felt that they learnt more about themselves (Reich & Kaplan, 1994). Similar effects were reported by participants in a study by Owen, Heyman, and Smith Slep (2006) who looked into the impact of participants completing questionnaires (Couples Conflict Protocols), engaging in conflict conversations and being interviewed individually about anger escalation and deescalation during these conversations. Both men and women rated the impact of the study as helpful to them personally and to their relationships.…”
Section: Literature About Interviewing Around Sensitive Topicssupporting
confidence: 61%
“…Participants have experienced a decrease in intrusive thoughts over time when compared to a control group (Lutgendorf & Antoni, 1999) or felt that they learnt more about themselves (Reich & Kaplan, 1994). Similar effects were reported by participants in a study by Owen, Heyman, and Smith Slep (2006) who looked into the impact of participants completing questionnaires (Couples Conflict Protocols), engaging in conflict conversations and being interviewed individually about anger escalation and deescalation during these conversations. Both men and women rated the impact of the study as helpful to them personally and to their relationships.…”
Section: Literature About Interviewing Around Sensitive Topicssupporting
confidence: 61%
“…Participants rated the typicality of their partner’s behavior on a 5-point scale ranging from 1 = much less than usual to 3 = about usual to 5 = much more than usual. Based on previous research (e.g., Foster et al, 1997; Owen, Heyman, & Smith Slep, 2006), two typicality subscales were scored: social support and social undermining. Cronbach’s alphas for the two subscales averaged across both discussions were .60 for social support (5 items) and .85 for social undermining (3 items).…”
Section: Methodsmentioning
confidence: 99%
“…Research with survivors of domestic violence and abusive relationships has found that some participants experience taking part in research as supportive (Campbell et al, 2010). In other studies, participants also reported the therapeutic benefits of being involved in research concerning conflict in relationships [personal communication from the English cohort of the study]; Owen et al, 2006). These benefits were commented upon in this study, for example, one female commented on the positive effect of being listened to and the opportunity to talk about her violent relationship.…”
Section: Safeguarding the Female Participant And Their Families-the Umentioning
confidence: 50%